The Impact of CSR on Customer Loyalty in Banking: The Role of Mediating Factors - Tomasz SZOPINSKI (Communications of International Proceedings, 2021)
The purpose of the current study is to examine the direct and indirect effects of Corporate Social Responsibility (CSR) activities undertaken by banks on consumer loyalty. Increasingly often, banks struggle to retain customers who are loyal to two or more brands.  CSR is an increasingly important issue in the international banking industry. Partial Least Square Structural Equation Modeling (PLS-SEM) technique using SmartPLS 3 was used to verify the relationships between the analyzed variables. The study was conducted on the inhabitants of Poland. Author identified service quality, customer satisfaction and word of mouth intention as significant mediators between perceived CSR activities and loyalty. In the case of corporate image, mediated effect was insignificant.
Keywords: Banking; customer retention; corporate social responsibility; loyalty